Effect of opioid treatment on clinical outcomes among cirrhotic patients in the United States. Issue 6 (16th March 2020) - Ali, Bilal; Jiang, Yu; Agbim, Uchenna; Kedia, Satish K.; Satapathy, Sanjaya K.; Barnes, Matthew; Maliakkal, Benedict; Nair, Satheesh P.; Eason, James D.; Gonzalez, Humberto C.
Abstract: Background: Opioid medications are frequently used to address pain among patients with cirrhosis, including those on the liver transplant (LT) waitlist and after transplantation. However, opioid use has been associated with poor allograft outcomes and reduced transplant survival. We examined the impact of opioid use across the spectrum of advanced liver disease, from the initial hepatology consultation for cirrhosis through transplant referral, listing, and the post‐LT process. Methods: The study includes all patients referred for cirrhosis management in a single healthcare system in the United States. Data were extracted retrospectively through medical chart review. Results: Of 414 patients included in the study, 104 (25%) were treated with opioid. Patients on opioids were more likely to be White, have body mass indices (BMI) >30, have HCV, suffer from hepatic encephalopathy, cigarette smokers, and use benzodiazepines concurrently. Higher doses of opioids were associated with multiple emergency department (ED). Eighty‐nine underwent LT, including 20 opioid‐treated patients. There was no difference found between the opioid and non‐opioid groups with regard to allograft loss, ED visits, and hospital readmissions at 2 years post‐LT follow‐up. Conclusions: Opioid treatment was common among patients with cirrhosis. We did not find increased negative outcomes among opioid users across the spectrum of cirrhosis. However, the sample for LT patients was small.